Penetration Testing Tangerang City Web Application With Implementing OWASP Top 10 Web Security Risks Framework - Armando, Yoel; Rosalina, Rosalina (Universitas Trilogi, 2023)
The speed of technological development has made it possible for all people to be connected to one another. The creation of web-based information systems that help in all areas, including government, health, and education, is one of the forces behind the development of technology. With these technological advancements, websites are susceptible to cybercrimes that could end in the theft of crucial data. Top 10 Web Application Security Risks is the most effective prevention process for decrease company information leaks. On the website tangerangkota.go.id, the researcher will conduct a test using the Top 10 Web Application Security Risks technique. Top 10 Web Application Security Risks consist of Broken Access Control, Cryptographic Failures, Injection, Insecure Design, Security Misconfiguration, Vulnerable and Outdated Components, Identification and Authentication Failures, Software and Data Integrity Failures, Security Logging and Monitoring Failures, Server-Side Request Forgery. The penetration testing results found on the Tangerang City website which are 4 injections, 2 broken access controls, 1 security misconfiguration.